State regulations in groundwater management: they bark but do they bite? - Molle, Francois; Closas, Alvar (2015)
Because of the logics of both colonization or de-colonization, the need to counter the anarchy of groundwater use, or the dissemination of global 'best practices' of IWRM, states have often assumed full ownership or custody of groundwater. Regulating groundwater use includes giving drilling and abstraction authorizations/licenses, establishing an inventory of wells and reducing use in existing wells. Although laws and regulations look neat and straightforward on paper, registration, regularization, and metering have been bedeviled by a host of logistical nightmares, policy contradictions, legal challenges, and vested private interests. The overall outlook is bleak and questions the overstating of state power in reordering groundwater use. Co-management with users, while in itself not sufficient to ensure success, often arises as a possible way out of the failure of state control.